Smart construction object. Tools for reprogramming the city - Riccardo Pollo; Matteo Giovanardi; Matteo Trane (Agathón)
The focus on the concept of Smart Cities in the shift towards circular development models derives from the ability to govern increasingly complex phenomena and processes. By introducing data-driven approaches, the information produced by ICT technologies allows us to ‘reprogram’ the functioning of the urban system, as a complex ecosystem in which matter and energy are continuously transformed. Starting from the analysis of research experiences carried out at the European level, this paper aims to explore potential and real barriers related to Smart Construction Objects in urban processes. Technological-digital integration, the use of data, and the emergence of new economic management models based on services are investigated with reference to façade systems, as components able to generate and share information to govern the input and output of the urban metabolic system.